Is bone mineral density in middle-aged and elderly individuals associated with their dietary patterns? A study based on NHANES - Runting, Huang; Qingyue, Luo; Yining, Yuan; Huiyu, Shu; Shu, Yang; Xixi, Feng (Frontiers in Nutrition, 2024)
Introduction Bone mineral density (BMD) is a crucial index for predicting fracture risk and diagnosing osteoporosis. With the global rise in osteoporosis prevalence, understanding the relationship between dietary patterns and BMD is vital for public health. This study aimed to explore the association between various dietary patterns and BMD among adults using data from the National Health and Nutrition Examination Survey (NHANES). Methods Data were analyzed from 8,416 NHANES participants aged 40 years and older across three non-consecutive survey cycles from 2013 to 2020. Dietary patterns were identified using a combination of factor analysis and cluster analysis. BMD measurements were then assessed, and associations with the identified dietary patterns were analyzed, with adjustments made for demographic variables. Results The analysis identified three distinct dietary patterns: “Low protein-High Dietary fiber-Vitamin A-Magnesium (LP-HDF-Vit A-Mg)”, “High macronutrient-Choline-Selenium (HM-Cho-Se)”, and “Low macronutrient-Vitamin D-Calcium (LM-Vit D-Ca)”, and then we found that women, older adults, and certain ethnic groups were at higher risk for low BMD. Participants adhering to the “HM-Cho-Se” and “LP-HDF-Vit A-Mg” dietary patterns exhibited significantly higher BMD compared to those following the “LM-Vit D-Ca” pattern. After adjusting for demographic variables, the “HM-Cho-Se” pattern remained positively associated with BMD, while the “LM-Vit D-Ca” pattern showed no significant association with BMD or the risk of low BMD. Discussion The findings suggest that adherence to the “HM-Cho-Se” dietary pattern may reduce the risk of low BMD, indicating potential synergies between these nutrients for bone health. However, the study has limitations, including the cross-sectional design and potential subjectivity in factor analysis. Future research should focus on longitudinal studies involving diverse age groups to better understand the causal relationship between dietary patterns and BMD. Despite these limitations, the study highlights the importance of dietary factors in maintaining bone health and suggests potential dietary interventions to reduce the risk of low BMD and osteoporosis.